Angiogenesis and Its Therapeutic Opportunities - So Young Yoo; Sang Mo Kwon (Mediators of Inflammation)
Angiogenesis plays critical roles in human physiology that range from reproduction and fetal growth to wound healing and tissue repair. The sophisticated multistep process is tightly regulated in a spatial and temporal manner by “on-off switch signals” between angiogenic factors, extracellular matrix components, and endothelial cells. Uncontrolled angiogenesis may lead to several angiogenic disorders, including vascular insufficiency (myocardial or critical limb ischemia) and vascular overgrowth (hemangiomas, vascularized tumors, and retinopathies). Thus, numerous therapeutic opportunities can be envisaged through the successful understanding and subsequent manipulation of angiogenesis. Here, we review the clinical implications of angiogenesis and discuss pro- and antiangiogenic agents that offer potential therapy for cancer and other angiogenic diseases.